PENGARUH LABA PER SAHAM, DEVIDEN PER SAHAM DAN MARGIN KEUNTUNGAN BERSIH TERHADAP HARGA SAHAM SUB SEKTOR BATUBARA DI BEI - Darman; Nanda; Mita Malisa (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This research aims to examine the influence of earning per share, dividen per share and net profit margin on share prices. The sample selection method in this research is the purposive sampling method. The data used is secondary data. The analytical method used is multiple linear regression analysis. Based on the results of hypothesis testing carried out in this research, it can be concluded that partially earning per share has a significant positive effect on share prices. Dividen per share has a significant positive effect on share prices. Net profit margin has no effect on share prices.